Estimation of the moisture content, volatile matter, ash content, fixed carbon and calorific values of saw dust briquettes - Francis Inegbedion (MANAS: Journal of Engineering)
“One way of making efficient use of existing resources is briquetting. Briquetting involves collecting combustible materials that are not usable due to lack of density, and compressing them into solid fuels of convenient shape that can be burnt like wood or charcoal”. “Biomass briquette is one of the proven ways of generating energy from waste”. “Fossil fuels, wood fuels and natural gas are the major sources for energy in Nigeria today”. “The excess use of these fuels will lead to serious environmental issues like global warming, air pollution and deforestation”. “This work is focused on estimating the heating values of sawdust briquettes to ascertain its suitability for domestic use and small-scale industrial cottage application”. “The results obtained shows that average percentage moisture content is 5.04%, average percentage volatile matter is 10.80%, average percentage ash content is 3.85%, average percentage fixed carbon is 80.95% and average percentage calorific value is 26918.02KCal/Kg. These results indicate that the briquettes made from sawdust have high heating value enough for domestic use and small-scale industrial cottage applications”.